2023
DOI: 10.1002/cphc.202200746
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Contributions of Charge Regulation to the Stability of Single Alpha Helices**

Abstract: The single alpha helix (SAH) is a recurring motif in biology. The consensus sequence has a di-block architecture that includes repeats of four consecutive glutamate residues followed by four consecutive lysine residues. Measurements show that the overall helicity of sequences with consensus E 4 K 4 repeats is insensitive to a wide range of pH values. Here, we use the recently introduced q-canonical ensemble, which allows us to decouple measurements of charge state and conformation, to explain the observed inse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…These particular sequences show the hallmarks of so-called single alpha helices (SAH), helices of length 25–200 residues frequently, though not exclusively, formed by (E 4 K 4 ) n repeats [9,33,34]. Below, we establish the evolutionary conservation of these regions, suggesting their structure, as well as high charge density, are likely to confer a fitness benefit.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…These particular sequences show the hallmarks of so-called single alpha helices (SAH), helices of length 25–200 residues frequently, though not exclusively, formed by (E 4 K 4 ) n repeats [9,33,34]. Below, we establish the evolutionary conservation of these regions, suggesting their structure, as well as high charge density, are likely to confer a fitness benefit.…”
Section: Resultsmentioning
confidence: 94%
“…The notion that intrinsically disordered proteins or regions sometimes adopt structure is well-understood [34], particularly in the case of folding upon binding [48]. Because of this distinction between conformations in isolation versus when bound to a partner, structures in the PDB may tell only a portion of the story.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because long D/E tracts are likely to extract entropic penalties associated with organizing water molecules around ionic moieties [ 158 ]. Further, the high linear charge density engenders intramolecular electrostatic repulsions that extract penalties in terms of conformational entropy [ 159 , 160 ]. These entropic penalties can be offset by neutralizing some of the charge, and the most efficient way to achieve this is through proton binding, which leads to upshifts of pK a values of acidic groups – a sequence-encoded emergent property known as charge regulation [ 160 , 161 ].…”
Section: Compositional Specificity and Idr Grammars Generate Distinct...mentioning
confidence: 99%
“…We hypothesized that the (PS(GS)4) linker following G75G76 in each Ub is too flexible to elicit change in conformation of M1-Ub4. Therefore, we installed sequences A(EA3K)3A or A(EA3K)6A which are predicted to be helical (Chen et al, 2013;Fossat et al) between the Ub units in a M1 (1-74) construct. SAXS data suggested that the structures of these M1-Ub4 constructs are significantly more extended compared to M1-Ub4 (1-76) as Rg values increased by nearly 10 Å (Table S2).…”
Section: Designed Linear(m1-linked) Polyub Chains With Longer Linkers...mentioning
confidence: 99%